2001
DOI: 10.1111/j.1365-2249.2001.01691.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of abnormal regulation of antibody response to coxsackievirus B4 antigen in prediabetic children

Abstract: SUMMARYEnterovirus infections are a potential environmental trigger of the autoimmune process leading to clinical type 1 diabetes. It has been suggested that the risk of virus-induced beta-cell damage might be connected with a defect in humoral immune responsiveness to enteroviruses. In the present study we assessed whether such a defect in IgG responsiveness to coxsackievirus B4 antigen existed in young children who developed diabetes-associated autoantibodies during prospective observation from birth until t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…Thus, it is very unlikely that any of these factors (or closely related factors) could have biased the comparisons between the case and control subjects. Fourth, in our previous studies, we have found that the regulation of antibody responsiveness to enterovirus antigens is quite normal in autoantibody-positive DIPP cases when analyzed after natural infections [Heino et al, 2001] or standardized immunization with inactivated poliovirus vaccine [Sadeharju et al, 2001]. This finding suggests that our results could not have been biased by abnormal immune responsiveness in case subjects.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, it is very unlikely that any of these factors (or closely related factors) could have biased the comparisons between the case and control subjects. Fourth, in our previous studies, we have found that the regulation of antibody responsiveness to enterovirus antigens is quite normal in autoantibody-positive DIPP cases when analyzed after natural infections [Heino et al, 2001] or standardized immunization with inactivated poliovirus vaccine [Sadeharju et al, 2001]. This finding suggests that our results could not have been biased by abnormal immune responsiveness in case subjects.…”
Section: Discussionmentioning
confidence: 54%
“…Infections, especially in early childhood, may in fact prevent or delay disease [86]. In some studies, the frequency of childhood infections correlated inversely with the incidence of T1D [87][88][89][90][91]. As one example, the EURODIAB Substudy 2 Study showed Pre-school day-care attendance and a proxy measure for total infectious disease exposure in early childhood was found to be inversely associated with diabetes [92].…”
Section: Selected Hypotheses On Non-specific Triggersmentioning
confidence: 99%
“…Serum samples were obtained when the first biopsy was taken (untreated coeliac disease), in remission on a gluten-free diet (treated), and/or at relapse after reintroduction of gluten (challenged). Anti-blactoglobulin antibody levels and avidities were analysed in sera from 16 children with untreated disease (median age 12 months, range [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and nine with treated disease (median age 35 months, range . Antigliadin antibody levels and avidities were measured in 16 untreated coeliac children (median age 15 months, range 10-24), 11 treated cases (median age 32 months, range 17-57) and in eight coeliac children at relapse on gluten challenge (median age 45 months, range 32-53).…”
Section: Patientsmentioning
confidence: 99%